Identification of Flight Performance RX-450 Series-5 - Hakiki, Hakiki; Duhri, Rahmat A.; A., Endro; Putro, Idris E.; Hakim, Arif N. (BRIN Publishing, 2022)
The performance of rocket flight can be evaluated from flight test data. The difference between flight prediction simulation and flight test data will indicate the accuracy of rocket identification model. Several factors cause rocket flight test deviated from flight prediction. Atmospheric disturbances and thrust scale are major factors causing inaccuracy rocket model. Another obstacle encountered is lack of flight data measured from flight test although there are still several data are obtained from accelerometer, altitude sensor, and GPS. Rocket performance identification can be obtained by conducting simulation of flight test data. This paper addresses identification of RX-450 series-5 in terms of flight performance. Thrust profile is generated from accelerometer recording data, and this parameter become an input for rocket simulation. The wind data is treated as atmospheric disturbance. The wind data is augmented by GPS on air balloon, and further processed become wind speed and win direction. Comparison both data can be explained as follow: During boost-phase, flight test data of the rocket shows maximum acceleration of 14.5g, on the other hand flight identification gives 13.4g. Rocket flies for 157.36 s in flight test whereas rocket identification predicts the max of flight time is 162.8 s. The rocket has max-range in 86.06 km measured by GPS data whereas flight identification estimates the max-range is 82.78 km. The flight identification indicates that the roket was deviated 6.25° from initial azimuth of the launcher direction. This 6.25° of deviation leads the rocket flies in Y-direction with the distance of 9.02 km. Flight test data shows that the rocket slides its direction 6° to the right of the initial launch azimuth.